Limnogeology: progress, challenges and opportunities: a tribute to Elizabeth Gierlowski-Kordesch - Rosen, Michael R.; Finkelstein, David B.; Park Boush, Lisa; Pla-Pueyo, Sila (Springer International Publishing, 2021)
Part1. Introduction -- Chapter1. Introduction to limnogeology: progress, challenges, and opportunities—A tribute to Elizabeth Gierlowski Kordesch -- Part2. African Lake -- Chapter2. Modern and ancient animal traces in the extreme environments of Lake Magadi and Nasikie Engida, Kenya rift valley -- Part3. European lakes -- Chapter3. Lake level fluctuations and allochthonous lignite deposition in the Eocene pull-apart basin “Prinz von Hessen” (Hesse, Germany) - A palynological study -- Chapter4. How changes of past vegetation and human impact are documented in lake sediments: Paleoenvironmental research in Southwestern Germany, a review -- Chapter5. Large-scale slumps and associated resedimented deposits in Miocene lake basins from SE Spain -- Chapter6. Lacustrine and fluvial microbialites in the Neogene of the Ebro Basin, Spain: a summary of up to date knowledge -- Part4. North America -- Chapter7. Ecological response of ostracodes (Arthropoda, Crustacea) to lake level fluctuations in the Eocene Green River Formation, Fossil Basin, Wyoming, USA -- Chapter8. History of Great Salt Lake, Utah, USA, since the termination of Lake Bonneville -- Chapter9. What’s new about the old Bonneville Basin? Fresh insights about the modern Limnogeology of Great Salt Lake -- Chapter10. Middle Holocene hydrologic changes catalyzed by river avulsion in Big Soda Lake, Nevada, USA -- Chapter11. Diatom record of Holocene moisture variability in the San Bernardino Mountains, California, USA -- Chapter12. A 12,000 year diatom-based palaeoenvironmental record from Lago de Zirahuén, Mexico -- Chapter13. Sedimentary record of the Zacapu Basin, Michoacán, México and implications for P’urhépecha Culture during the Pre-Classic and Post-Classic Periods -- Chapter14. Stratigraphy and Sedimentology of the Upper Pleistocene to Holocene Lake Chalco drill cores (Mexico Basin) -- Chapter15. Submarine groundwater discharge as a catalyst for eodiagenetic carbonate cements within marine sedimentary basins -- Part5. South America -- Chapter16. Reconstructing paleoenvironmental conditions through integration of paleogeography, stratigraphy, sedimentology, mineralogy, and stable isotope data of lacustrine carbonates—an example from early Middle Triassic strata of southwest Gondwana, Cuyana Rift, Argentina -- Part6. Asia -- Chapter17. Modern sedimentary systems of Qinghai Lake -- Chapter18. Freshwater microbialites in Early Jurassic fluvial strata of the Pranhita-Godavari Gondwana Basin, India.
Keywords: Sedimentologie; Seesediment; Historische Geologie; Limnologie; Sedimentation; See; Paläolimnologie